KARAKTERISTIK MUARA SUNGAI MALALAYANG YANG BERDAMPAK PADA BANTARAN BANJIR - Kenet S.W. Tumurang; Zetly Tamod; Lientje Th. Karamoy; Meldy Sinolungan (COCOS, 2015)
Abstract This study aims to determine the characteristics of the estuary Malalayang which have an impact on the floodplain. This research was conducted by using the method of identification by viewing the variables that affect observations floodplain. Characteristics estuaries studied the nature of the estuary of the river, the water discharge, water quality, sedimentation and tidal. How to get the data through (1) Software ArcView to calculate the slope of the river and see Malalayang watershed flow patterns, the high point seen in RBI Map Scale 1: 50,000 Sheet 2417-23. Elevation Map / Contour Manado City used to look bathymetry of the estuary Malalayang. (2) Water discharge is obtained by the equation Q = V.A. (3) Water Quality visits with Tracer tool Pocketester pH, TDS and Salt. (4) The precipitation data obtained from BMKG Kayuwatu. (5) Data obtained from sediment trap sediment. The results showed that the characteristics of estuary Malalayang impact on floodplain: (1) the type tidal estuary leaning daily Malalayang dual pairs occur more frequently so that the deposition of sediment is more going on than spending sediments to the sea (sediment volume measured during the first month ie 294 372 cm3). (2) The pattern of flow in the watershed Malalayang is a dendritic pattern so that the discharge of water from upstream and water at high tide in the estuary can be restrained so that when the estuary Malalayang no longer able to accommodate the volume of water, then an overflow into the floodplain. (3) Bathymetry Coastal Estuary Malalayang Malalayang which is at a steep conditions. Â Keywords: Estuary, Tidal, Sediment, Bathymetry